2019
DOI: 10.1111/jfbc.12821
|View full text |Cite
|
Sign up to set email alerts
|

HPLC‐QTOF‐MS/MS profiling, antioxidant, andα‐glucosidase inhibitory activities ofPyracantha fortuneanafruit extracts

Abstract: This study was carried out to optimize the solvent for extracting the antioxidants and α‐glucosidase inhibitors (AGIs) from Pyracantha fortuneana fruit (PFF) and the major chemical components were characterized by HPLC‐QTOF‐MS/MS. The results showed that 50% and 70% acetone (v/v, ml/ml) gave the best extraction efficiency on phenolics and total flavonoids, while 70% acetone and 50% methanol possess better recovery on protein and polysaccharides, respectively. In addition, the 50% and 70% acetone extracts gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Li, a wild evergreen shrub or small arbour belonging to the Pyracantha of Osaceae apple subfamily, is mainly distributed in areas from eastern Asia to southern Europe. Pyracantha fortuneana fruit (PFF), as a new food resource, has become a research hotspot due to its rich nutrients and natural active ingredients, and it is even treated as a staple food in some areas in case of food shortage (Wei et al ., 2017; Wang et al ., 2019). However, most PFF are wild fruits, with several disadvantages for eating, such as small fruit size, rough and astringent taste, fresh fruit seasonality and intolerance to storage.…”
Section: Introductionmentioning
confidence: 99%
“…Li, a wild evergreen shrub or small arbour belonging to the Pyracantha of Osaceae apple subfamily, is mainly distributed in areas from eastern Asia to southern Europe. Pyracantha fortuneana fruit (PFF), as a new food resource, has become a research hotspot due to its rich nutrients and natural active ingredients, and it is even treated as a staple food in some areas in case of food shortage (Wei et al ., 2017; Wang et al ., 2019). However, most PFF are wild fruits, with several disadvantages for eating, such as small fruit size, rough and astringent taste, fresh fruit seasonality and intolerance to storage.…”
Section: Introductionmentioning
confidence: 99%
“…The total flavonoid extract of Nelumbo nucifera leaf showed inhibitory activity against α ‐amylase and α ‐glucosidase with IC 50 values of 2.20 and 1.86 mg/ml (Liu et al, 2013). The 50 and 70% acetone extracts of Pyracantha fortuneana fruit with higher phenolic and flavonoid contents showed higher α ‐glucosidase inhibitory activity than methanol and ethanol extracts (Wang et al, 2018). The results of our study seemed to agree with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed the presence of phytochemicals, like glycosides, carbohydrates, steroids, flavonoids, phenolics, resins and tannins in Pyracantha spp. (18,(29)(30)(31). For example, Fico, A (32) found phenolic acids, such as hyperoside, isoquercitrin, quercetin and rutin in P. coccinea fruits.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…Wang, Ye (31) with the help of high-pressure liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC-QTOF-MS/MS) profiling identified 7 flavonoids, 6 phenolic acids, 7 organic acids, 3 tannins, 1 terpene, and 1 alkaloid from P. fortuneana fruit (50% acetone extract) and reported antioxidant and α-glucosidase inhibitory activities. Wei, Chai (50) extracted proanthocyanidins from P. fortuneana fruit and reported α-glucosidase inhibition (IC 50 0.15 µg/mL) in a non-competitive manner.…”
Section: Pyracantha Fortuneana (Maxim) H L Limentioning
confidence: 99%